P80 LONG-TERM OUTCOMES OF CLINICAL AND PATHOLOGICAL-STAGED T3N3 ESOPHAGEAL CANCER. (23rd November 2019) - Kamarajah, S K; Newton, N; Navidi, M; Wahed, S; Immanuel, A; Hayes, N; Griffin, S M; Phillips, A W
Abstract: Objective: The aim of this study was to determine the outcomes of patients with T3N3 esophageal cancers and determine differences between the clinical stage and pathological stage. Background: Locally advanced esophageal cancer is associated with poor long-term survival. Pre-treatment and post-treatment stage may differ due to the effect of neoadjuvant therapy and inaccuracies in staging. Multimodality staging followed by discussion at an MDT is considered the gold standard. Despite this, patients can be under-staged or over-staged leading to inadequate or unnecessary treatment associated with high levels of morbidity. Methods: Consecutive patients from a single unit between 2010 - 2018 were included with either clinical (cT3N3) or pathological (pT3N3) esophageal cancer. Outcomes were compared between patients that underwent transthoracic esophagectomy and radical two field lymphadenectomy with or without neoadjuvant treatment and those patients staged cT3N3 treated non-surgically (NSR). Demographics, clinical and pathological stage, histological information and outcomes were recorded. Patients were staged using the TNM 8. Results: This study included 156 patients, of which 63 had non-surgical treatment, only 3 of these had radical treatment. Of the remaining 93 patients who underwent esophagectomy, 34 were cT3N3, 54 were pT3N3 and five were unchanged before and after treatment. Median overall survival (OS) for surgical cT3N3 patients was significantly longer than pT3N3 and NSR (median: NR vs 19 vs 8 months, p<0.001). Twenty-seven patients with cT3N3 had lower staging following treatment whilst 3 had a higher stage. Conclusion: T3N3 disease carries a poor prognosis. Within this cohort cT3N3 disease treated surgically has a high 5-year overall survival suggesting possible over-staging and stage migration due to neoadjuvant therapy. To contrast this those not having surgery have a dismal prognosis. The impact of neoadjuvant treatment cannot be predicted and, current staging modalities may be inaccurate. Clinical stage should be used with caution when counselling patients regarding management and prognosis.